Kontroversi Spirit Doll dan Spirit Ketauhidan: Analisis Pesan Para Da’I terkait Fenomena Spirit Doll - Lukman Hakim (Institut Agama Islam Tribakti (IAIT) Kediri, 2022)
The phenomenon of spirit dolls has recently become a hot topic of discussion. Many people treat this doll as if it were a baby, lavishing it with love and attention. It is the positive feedback from its users that has increased its popularity, and the price is also rising. Researchers investigated this using a qualitative approach and library research methods, focusing on the responses of the da'I and Islamic organizations to this spirit doll. As a result, the da'i studied all agreed that playing with and caring for the doll was permissible as long as it did not become excessive and became a wasilah to gain the glory and happiness of living in the world. The preachers gave teachings that addressed three different aspects: cognitive, emotive, and psychomotor. The da'i have imparted a great deal of information regarding dolls, spirits, and their many dimensions in a clear and obvious manner. The da'i also cautioned Muslims against becoming entangled in trends that could lead to polytheism. Finally, the da'i recommended people to make the most of their resources, energy, and time so that they can be channeled to the clear and good, such as caring for orphans, paying recompense and donations to those who are entitled, and a variety of other qualities.